(untitled) (Journal of Geography and Environmental Management, 2018)
Even though online shopping is becoming increasingly popular, many consumers are still reluctant to buy online. One approach to improve adaption is to base e-commerce search engines on ontologies to allow a more intuitive search process. This paper presents the results of an analysis how a sample of online shoppers perceived various ontology-based features in an online shop. The data was gathered in two focus groups with panelists coming from different socio-demographic backgrounds. Most middleaged women actively buy through catalogs. However, across the focus groups, most panelists are very reluctant buying online. Our study suggests that age has a higher influence on the information search behaviour of consumers in online shops than gender.